Internship and innovation program under the Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA) project in Zambia - Minh, Thai Thi; Jacobs-Mata, Inga; Mutenje, Munyaradzi; Pele, Winnie; Ngowenani, Nohayi; Muzungaire, Lizzy (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The Accelerating Impact of CGIAR Climate Research for Africa (AICCRA) project works to deliver a climate-smart African future driven by science and innovation in agriculture. AICCRA does this by enhancing access to climate information services (CIS) and climate-smart agricultural (CSA) to millions of smallholder farmers in Africa. Under AICCRA-Zambia, the International Water Management Institute (IWMI) partners with national universities and private sector entities to implement the internship and innovation grant program with the private sector (I2G program) to generate capabilities of individuals and institutions to deliver on the ‘translational research’ into business and commercialization. The I2G program supports young entrepreneurs and young professionals through the private sector working experience and demand-driven innovation development. The overall objective of I2G program is to build greater trust, knowledge sharing, and collaboration between the private sector, public sector, and research institutions that, in turn, contribute to an enabling environment to scale CSA-CIS bundles in an economically and environmentally sustainable way. Specific objectives of the I2G program include: support young entrepreneurs and young professionals through the private sector working experience and demand-driven innovation development; catalyze contextually relevant technical, social and financial innovations to support CSA-CIS scaling; create scientific evidence to catalyze innovative approaches to CSA agribusiness; create and foster national research – private sector partnerships to catalyze CSA-CIS scaling; and strengthen systemic capacity to be responsive and inclusive to scaling of CSA-CIS bundles. The I2G program has been implemented through five modalities: the internship with private sector entities, CSA-CIS hackathon for innovation development, business incubation for innovation commercialization, CSA-CIS demand-driven research, and CSA-CIS integration into educational curriculums. Centre to these modalities is the co-identification of CSA-CIS-related needs and challenges in relation to CSA-CIS scaling in Zambia which private sector actors, including smallholder farmers, are facing with.